Coproductive capacities: Rethinking science-governance relations in a diverse world - Lorrae E. van Kerkhoff (2018)
© 2015 by the author(s). Tackling major environmental change issues requires effective partnerships between science and governance, but relatively little work in this area has examined the diversity of settings from which such partnerships may, or may not, emerge. In this special feature we draw on experiences from around the world to demonstrate and investigate the consequences of diverse capacities and capabilities in bringing science and governance together. We propose the concept of coproductive capacities as a useful new lens through which to examine these relations. Coproductive capacity is “the combination of scientific resources and governance capability that shapes the extent to which a society, at various levels, can operationalize relationships between scientific and public, private, and civil society institutions and actors to effect scientifically-informed social change.” This recasts the relationships between science and society from notions of “gaps” to notions of interconnectedness and interplay (coproduction); alongside the societal foundations that shape what is or is not possible in that dynamic connection (capacities). The articles in this special feature apply this concept to reveal social, political, and institutional conditions that both support and inhibit high-quality environmental governance as global issues are tackled in particular places. Across these articles we suggest that five themes emerge as important to understanding coproductive capacity: history, experience, and perceptions; quality of relationships (especially in suboptimal settings); disjunct across scales; power, interests, and legitimacy; and alternative pathways for environmental governance. Taking a coproductive capacities perspective can help us identify which interventions may best enable scientifically informed, but locally sensitive approaches to environmental governance.